1984
DOI: 10.1161/01.res.54.4.447
|View full text |Cite
|
Sign up to set email alerts
|

Identification of vascular postsynaptic alpha 1- and alpha 2-adrenoceptors in man.

Abstract: SUMMARY. We studied postsynaptic a-adrenoceptors in human blood vessels by measuring the influence on forearm blood flow induced by intra-arterial infusions of selective a t -and a 2 -adrenoceptor agonists (methoxamine, B-HT 933, clonidine and guanfacine) and antagonists (doxazosin and yohimbine). The studies were done in healthy volunteers, and forearm blood flow was measured by plethysmography. All agonists produced a significant and dose-dependent vasoconstriction. The effect of B-HT 933 was completely abol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
30
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 33 publications
8
30
0
Order By: Relevance
“…1843 These findings, together with the results from our study, indicate that also in humans postsynaptic a 2 -adrenergic (in addition to a,-adrenergic) receptors contribute substantially to the adrenergic sympathetic and humoral regulation of capacitance vessel tone. This would complement the role of this receptor type in the control of arteriolar tone in humans 13 and extend the evidence that sympathetic and humoral adrenergic activation act on two types of vascular a-adrenergic receptors, of which one (the vascular a 2 -adrenergic receptor) seems to be preferentially modulated by various physiological and pathophysiological factors.…”
supporting
confidence: 63%
“…1843 These findings, together with the results from our study, indicate that also in humans postsynaptic a 2 -adrenergic (in addition to a,-adrenergic) receptors contribute substantially to the adrenergic sympathetic and humoral regulation of capacitance vessel tone. This would complement the role of this receptor type in the control of arteriolar tone in humans 13 and extend the evidence that sympathetic and humoral adrenergic activation act on two types of vascular a-adrenergic receptors, of which one (the vascular a 2 -adrenergic receptor) seems to be preferentially modulated by various physiological and pathophysiological factors.…”
supporting
confidence: 63%
“…48 Our finding that insulin, at plasma levels comparable to those observed in the postprandial state, attenuates selectively the increase in FVR induced by an a 2 -adrenergic agonist could indicate that the cross talk between the hormone and the sympathetic nervous system at the vascular level occurs through a well-identified vasoconstrictive signal transduction pathway. The observation that insulin infusion is able to abolish the reflex forearm vasoconstriction induced by graded LBNP during intra-arterial prazosin treatment supports this conclusion and may be in keeping with the hypothesis that a 2 -adrenergic receptors participate in the mediation of vasoconstriction elicited by increased endogenous catecholamine levels.…”
Section: Discussionmentioning
confidence: 71%
“…In the present study the a,-adrenergic blocking effect of ketanserin was confirmed by the finding that it significantly reduced the vasoconstrictor response to the selective a,-agonist methoxamine. 49 Similar results were found for tyramine, which acts as an indirect agonist of a-adrenergic receptors by displacing norepinephrine from the sympathetic nerve endings, 50 ' 5I thus providing evidence that ketanserin also is able to counteract a vasoconstrictor response induced by endogenously released norepinephrine. Although the a r blocking effect of ketanserin has been regarded as weak by several investigators, 23 ' 52~54 the present study clearly showed that this effect of ketanserin in this particular vascular bed occurred at lower doses than are needed for 5-HT 2 blockade (see Figures 5 and 6).…”
mentioning
confidence: 60%